Animals and society : an introduction to human-animal studies. - DeMello, Margo (Columbia University Press, 2021)
Human-animal studies is an interdisciplinary field that explores the spaces that animals occupy in human social and cultural worlds. Margo DeMello provides a broad overview of this rapidly growing field. This second edition is fully updated and expanded throughout, enhancing the book's relevance for student and activist readers alike.
Keywords: Animals and civilization -- History.; Human-animal relationships -- History.; Human-animal relationships.; Animaux et civilisation -- Histoire.; Relations homme-animal -- Histoire.; Relations homme-animal.; NATURE / Animal Rights.; Animals and civilization; Human-animal relationships; Human-Animal Studies.; animal cruelty.; animal ethics.; animals and society.; philosophy of animals.; veganism.; History